2020
DOI: 10.1038/s41598-020-74555-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of viral pathogens causing upper respiratory tract infections among symptomatic children in Mwanza, Tanzania

Abstract: Upper-respiratory tract infections (URTI) are the leading causes of childhood morbidities. This study investigated etiologies and patterns of URTI among children in Mwanza, Tanzania. A cross-sectional study involving 339 children was conducted between October-2017 and February-2018. Children with features suggestive of URTI such as nasal congestion, dry cough, painful swallowing and nasal discharge with/without fever were enrolled. Pathogens were detected from nasopharyngeal and ear-swabs by multiplex-PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Rhinoviruses are the most common cause of ARI in all age groups (36)(37)(38)(39), which poses a significant burden for the health care system, as well as a substantial economic loss caused by absenteeism (40). Although they lead in the aetiology of ARI, they have been neglected for years for a number of reasons: (i) they were seen as rare (or improbable) causative agents of lower respiratory tract infections (LRTIs) since their replication is difficult at temperatures above 33 • C; (ii) because they cause self-limiting upper respiratory tract infections (URTIs) in healthy individuals, do not cause hospitalization and, consequently, do not burden the hospital system; (iii) until the development of molecular detection methods the laboratory diagnosis of these viruses was relatively slow, therefore clinically irrelevant and expensive, and; (iv) to date there is no commercially available effective specific antiviral therapy or vaccine specifically targeting rhinovirus (41).…”
Section: Rhinovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhinoviruses are the most common cause of ARI in all age groups (36)(37)(38)(39), which poses a significant burden for the health care system, as well as a substantial economic loss caused by absenteeism (40). Although they lead in the aetiology of ARI, they have been neglected for years for a number of reasons: (i) they were seen as rare (or improbable) causative agents of lower respiratory tract infections (LRTIs) since their replication is difficult at temperatures above 33 • C; (ii) because they cause self-limiting upper respiratory tract infections (URTIs) in healthy individuals, do not cause hospitalization and, consequently, do not burden the hospital system; (iii) until the development of molecular detection methods the laboratory diagnosis of these viruses was relatively slow, therefore clinically irrelevant and expensive, and; (iv) to date there is no commercially available effective specific antiviral therapy or vaccine specifically targeting rhinovirus (41).…”
Section: Rhinovirusesmentioning
confidence: 99%
“…Rhinoviruses are estimated to cause more than half of URTIs usually presenting as common cold syndrome; however, during the last two decades, numerous studies have revealed their role as leading causes of LRTIs ( 38 , 39 , 43 , 44 ). A recent prospective study conducted in 11 European countries has shown that in adults presenting to primary care with LRTI, the most common viral pathogens detected were human rhinoviruses (20.1%) ( 45 ).…”
Section: An Overview and Global Trendsmentioning
confidence: 99%
“…An investigation of 452 children with acute respiratory infection reported that acute respiratory infection in children was mainly infected by HRV (11.28%), and most of the HRV infection occurred was in winter 7 . Respiratory virus surveillance studies showed that the positive rate of HRV was 16.4%–35.1% 8–13 . During the COVID‐19 pandemic, the government had taken all possible means to stop the pandemic, and successfully stopped the COVID‐19 pandemic in Guangzhou, and the common respiratory infectious diseases, such as influenza and pneumonia as well 3 .…”
Section: Characteristics School a School B School C School D School Ementioning
confidence: 99%
“…ARIs are the most frequent type of infection during the first 3 years of life, with a median of 10 episodes per child (with up to 90% corresponding to AURIs) ( Vissing et al, 2018 ). Viruses are the primary cause of both AURIs and ALRIs in children, with rhinovirus the most common cause of AURI ( Kwiyolecha et al, 2020 ) and respiratory syncytial virus the most common cause of ALRI ( O’Brien et al, 2019 ; Li et al, 2021 ). Influenza virus causes seasonal global epidemics, representing an important cause of ALRIs associated with hospitalization and severe outcomes in children aged <5 years as compared to older children and adults ( Ruf and Knuf, 2014 ; Wang et al, 2020 ).…”
Section: Gut Microbiota and Respiratory Infections During Early Childhoodmentioning
confidence: 99%